2019
DOI: 10.1111/jssr.12609
|View full text |Cite
|
Sign up to set email alerts
|

What's Behind the “Nones‐sense”? Change Over Time in Factors Predicting Likelihood of Religious Nonaffiliation in the United States

Abstract: The proportion of people in the United States who identify as unaffiliated with any religious tradition (Nones) has risen steadily since the 1990s. Empirical investigations have examined this phenomenon, and point to a range of sociodemographic and associational variables as significant predictors of religious nonaffiliation. To build on these, the research reported here uses nearly five decades of General Social Survey data and binary logistic regression to examine change over time in the direction and size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, recent research has shown that the religiously unaffiliated in the US are becoming more and more representative of the population as a whole (Strawn 2019). The most obvious explanation for this is that the nonreligious are becoming an increasingly large segment of the entire population.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…However, recent research has shown that the religiously unaffiliated in the US are becoming more and more representative of the population as a whole (Strawn 2019). The most obvious explanation for this is that the nonreligious are becoming an increasingly large segment of the entire population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the nonreligious expand in size, they must necessarily begin to look like the population in general because they are more of the population. Strawn (2019) shows that several formerly important correlates of disaffiliation are no longer strong correlates, such as age, sex, educational attainment, and income. While atheists -a subset of the nonreligious -remain distinct in a number of ways (Cragun 2014), the growth of the nonreligious in the US has reduced the distinctiveness of the nonreligious, just as it has done in other countries where the nonreligious have seen rapid growth, such as Canada (Thiessen & Wilkins-Laflamme 2017 and the UK (Voas & McAndrew 2012;Voas 2015;Voas & Crockett 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations